Influencia del procedimiento técnico – científico desarrollado por los peritos de la Policía Nacional del Perú, jurisdicción Chiclayo, en delitos de violación sexual durante el 2022 - Donet Córdova, Katherine Nicole (2023)
The influence of the technical-scientific procedure developed by the experts of the National Police of Peru, Chiclayo jurisdiction, in crimes of rape during 2022 took place during the months of October and November of the same year. Using the techniques of survey and Likert scale, the sample is made up of 60 police experts who work in the criminalistics office (OFICRI-CHICLAYO). The influence of the technical-scientific procedure developed by the experts of the National Police of Peru, Chiclayo jurisdiction, on crimes of rape during 2022 was determined through the preparation of graphs and statistical validation. It was determined that the technical-scientific procedure influences the inspections for rape at a significance level of 5%, with a value of 0.860 indicating that a better technical-scientific procedure leads to a better inspection for rape.